2021
DOI: 10.1371/journal.pntd.0009205
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance in dengue vectors from hotspots in Selangor, Malaysia

Abstract: Background In Malaysia, dengue remains a top priority disease and usage of insecticides is the main method for dengue vector control. Limited baseline insecticide resistance data in dengue hotspots has prompted us to conduct this study. The present study reports the use of a map on the insecticide susceptibility status of Aedes aegypti and Aedes albopictus to provide a quick visualization and overview of the distribution of insecticide resistance. Method and results The insecticide resistance status of Aedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…When this point reached, such resistant mosquitoes were predicted to be survived. Likewise, similar results were also reported in Rasli et al (2021). Therefore, those populations characterised with high or moderate MFO enzyme activities with less or no impact of PBO along with insecticide pyrethroids, should be further investigated, especially on the significance of kdr gene in the development of insecticide resistance.…”
Section: Discussionsupporting
confidence: 77%
“…When this point reached, such resistant mosquitoes were predicted to be survived. Likewise, similar results were also reported in Rasli et al (2021). Therefore, those populations characterised with high or moderate MFO enzyme activities with less or no impact of PBO along with insecticide pyrethroids, should be further investigated, especially on the significance of kdr gene in the development of insecticide resistance.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, recent studies conducted in dengue hotspot areas of Selangor emphasised possible risks to the success of insecticides presently implemented in dengue vector control. Rasli et al [ 18 ] studied the largest dengue hotspot areas, with about 24 different dengue hotspot areas. They showed high and significant insecticide-resistant to pyrethroid and organophosphate.…”
Section: Discussionmentioning
confidence: 99%
“…In Penang Island, Zuharah et al [ 19 ] reported the risk of developing insecticide resistance towards pyrethroid with around 87% mortality rates towards permethrin in the Northern district of Penang. Rasli et al [ 18 ] and Zuharah et al [ 19 ] indicated insecticide resistance in Ae . aegypti in the dengue hotspot areas similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term use of temephos has given rise to resistant strains in Ae. aegypti mosquito populations in various countries, such as recent reports in Brazil 8 , Cuba 9 , Indonesia 10 , Malaysia 11 and Peru 12 , in addition to genotoxic effects in humans 13 .…”
Section: Introductionmentioning
confidence: 99%